Mythologising culture: Part 1: Desiring Aboriginality in the suburbs1 - Cowlishaw, Gillian (The Australian journal of anthropology, 2010)
In western Sydney, I found an extreme version of what I propose is a national Aboriginal mythopoeia, that is, a powerful system of beliefs and practices in relation to Aboriginal people and culture. A reified Aboriginal culture is promoted at institutional sites and in reconciliation discourses that evokes the presence of something precious and mysterious that must be re-read into local Aboriginal people, but which assiduously avoids their actual circumstances and subjectivities. The awkward relationships and avoidances evident in a western Sydney reconciliation group are posited as a benign example of this mythology, born of a ‘sentimental politics’ of regret and reparation at work in Australia. Unity between the state and civil society is evident here, thus requiring an analysis that goes beyond a critique of government policies and programmes as intentional and rational, and grasps the nature of the widespread desire for Aboriginality. Through ethnographic attention to the actual relationships of Indigenous people and others, anthropologists can avoid being complicit in this regressive, separatist construction.